Symbolic Violence In Educational Institutions in Indonesia; Case Study of Private High School in Padang City, West Sumatera - Yenni Melia (Indonesian Journal of Religion and Society, 2022)
This research is motivated by many occurrences of symbolic violence in educational institutions, especially in Private Schools of Padang. Symbolic violence that is often found in schools in the form of speech or words that can cause mental damage to students sometimes also it can make fight between students. The purpose of the study was to describe : the form and efforts of schools in overcoming symbolic violence that occurred in City Private High Schools. The approach used in this research is a qualitative approach with descriptive research type, the technique used for data collection is by interview, observation and document study. In addition, the selection of informants in this study were private high school students in Padang City. The number of informants was 40 students consisting of SMA Baituramah and SMA PGRI 1 Padang. Data analysis used interactive data from Miles Huberman. The results of the research on symbolic violence in schools are in the form of a) symbolic violence in verbal form, namely symbolic violence that is displayed in the form of words, for example, often ridiculing or harsh words, b) Through non-verbal or actions, namely in the form of actions such as throwing paper and ink so as to make clothes. dirty students. Meanwhile, the effort to overcome this is the provision of sanctions by schools, namely teachers and school principals. The conclusion that symbolic violence allowed or justified which can damage the character or mentality of students.